2001
DOI: 10.1002/1521-3773(20010119)40:2<451::aid-anie451>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Preferred Twist in a Biphenyl Core by Stereogenic Centers: A Novel Approach to the Absolute Configuration of 1,2- and 1,3-Diols

Abstract: A quick, simple, and reliable method to assign the absolute configuration of 1,2‐ and 1,3‐diols: all that is needed is to measure the CD sign of the A band (250 nm) of their biphenyldioxolanes 1 (n=0, 1). The chirality of the diol induces a preferred sense of twist in the biphenyl moiety (R,R→M and S,S→P), and a positive A band (a probe of M twist) reveals an R or R,R configuration of the diol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
64
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 61 publications
(2 reference statements)
4
64
0
Order By: Relevance
“…The consistently positive Cotton effects at longer wavelengths and negative Cotton effect at shorter wavelengths are typical of the (S) compound, whereas an opposite CD pattern is exhibited by the (R) compound. [56] Therefore, as in the related Bin derivatives and peptides, [27] the CD spectrum reflects the configurational properties of the [20-C-6]-Bip residue, but does not provide any conformational information. …”
Section: Conformational Characterization Of Boc-[20-c-6]-bip-(aib) 6 supporting
confidence: 54%
“…The consistently positive Cotton effects at longer wavelengths and negative Cotton effect at shorter wavelengths are typical of the (S) compound, whereas an opposite CD pattern is exhibited by the (R) compound. [56] Therefore, as in the related Bin derivatives and peptides, [27] the CD spectrum reflects the configurational properties of the [20-C-6]-Bip residue, but does not provide any conformational information. …”
Section: Conformational Characterization Of Boc-[20-c-6]-bip-(aib) 6 supporting
confidence: 54%
“…Moreover, we have recently demonstrated that the NMR-based Mosher approach is sometimes not reliable in the AC assignment to chiral diols, 30 whereas chiroptical methods, that is, ECD, vibrational circular dichroism (VCD), and optical rotatory dispersion (ORD), can provide more general and reliable tools for this task. 31 At first, we attempted to apply for AC assignment to 1 and 2 the use of biphenyl chiroptical probes, 32,33 that we recently demonstrated to be particularly straightforward for naturally occurring diols. 30 However, compounds 1 and 2 did not allow biphenyl derivatization, as a consequence of their low solubility in the required aprotic solvents.…”
Section: Resultsmentioning
confidence: 99%
“…However, a significant limitation of this approach can occur in systems undergoing conformational changes and in applications to acyclic compounds. The flexibility of such systems may cause difficulties in the correct stereochemical assignment [21][22][23].…”
Section: Introductionmentioning
confidence: 91%